2021
DOI: 10.1136/jitc-2021-002722
|View full text |Cite
|
Sign up to set email alerts
|

IGF1 receptor inhibition amplifies the effects of cancer drugs by autophagy and immune-dependent mechanisms

Abstract: BackgroundPharmacological autophagy enhancement constitutes a preclinically validated strategy for preventing or treating most major age-associated diseases. Driven by this consideration, we performed a high-content/high-throughput screen on 65 000 distinct compounds on a robotized fluorescence microscopy platform to identify novel autophagy inducers.ResultsHere, we report the discovery of picropodophyllin (PPP) as a potent inducer of autophagic flux that acts on-target, as an inhibitor of the tyrosine kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…IGF1R can inhibit AMPK activity via Akt1, which phosphorylates an AMPK inhibitory site [ 54 ] ( Figure 8 ). Picropodophyllin has been recently discovered as a potent inducer of autophagic flux that acts on-target [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…IGF1R can inhibit AMPK activity via Akt1, which phosphorylates an AMPK inhibitory site [ 54 ] ( Figure 8 ). Picropodophyllin has been recently discovered as a potent inducer of autophagic flux that acts on-target [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been some evidence that targeting the IGF1 pathway may be effective in controlling a variety of cancers. An IGF1 inhibitor could strongly control cell growth of ER positive breast cancer cells 30 .Targeting IGF1R ampli es the effects of chemotherapy via autophagy and immune-dependent mechanisms in triple-negative breast cancer 31 . Some researchers have developed IGF1R targeted theranostic nanoparticles for precision therapy of pancreatic cancer 32 .However, there is still a lack of relevant researches in OC, especially in OCCC.…”
Section: Discussionmentioning
confidence: 99%
“…Guido Kroemer, Université de Paris, France, pointed out that caloric restriction mimetics enhances autophagy which improves longevity. Additionally, caloric restriction mimetics can be used in the treatment of diseases such as cancer; here the Kroemer group showed that the IGF1R inhibitor picropodophyllin enhance the efficacy of chemoimmunotherapy by stimulating immunosurveillance in mice [24,25]. Valter Longo, USC Davis School of Gerontology, USA, discussed fasting mimicking diets in relation to vitamin C treatment of cancer cells.…”
Section: The Benefits Of Dietary Restrictionmentioning
confidence: 99%